Fatty acid composition of hempseed oils from different locations in Turkey - Kiralan, M.; Gül, V.; Metin Kara, S. (Spanish Journal of Agricultural Research, 2010)
Recent interest in hempseed as a source of food has largely focused on its oil content and fatty acid profile. The oil content and fatty acid composition (15 fatty acids) of twenty one different hempseed samples of domestic origin from north-western Turkey were monitored. The samples were obtained from seed wholesalers and local spice shops and are of unknown genetic origin. The oil content of the hempseeds ranged between 29.6 to 36.5%. Out of the 15 detected fatty acids, the omega-6 linoleic acid (18:2n-6) was predominant and fluctuated from 55.4 to 56.9%, while the omega-3 α-linolenic (18:3n-3) acid ranged from 16.5 to 20.4% and the omega-9 oleic acid (18:1n-9) ranged from 11.4 to 15.9%. Of the minor fatty acids, the highest concentrations were found for γ-linolenic acid (18:3n-6), range 0.6-1.1%, followed by stearidonic acid (18:4n-3), range 0.3-0.5%. These results show that hempseed grown in north-western Turkey provides a well balanced and rich source of dietary omega-6 and -3 essential fatty acids and appears to be a potentially valuable source of food.